Effective inhibition of MERS-CoV infection by resveratrol. Issue 1 (December 2017) - Lin, Shih-Chao; Ho, Chi-Tang; Chuo, Wen-Ho; Li, Shiming; Wang, Tony; Lin, Chi-Chen
Abstract Background Middle East Respiratory Syndrome coronavirus (MERS-CoV) is an emerging viral pathogen that causes severe morbidity and mortality. Up to date, there is no approved or licensed vaccine or antiviral medicines can be used to treat MERS-CoV-infected patients. Here, we analyzed the antiviral activities of resveratrol, a natural compound found in grape seeds and skin and in red wine, against MERS-CoV infection. Methods We performed MTT and neutral red uptake assays to assess the survival rates of MERS-infected Vero E6 cells. In addition, quantitative PCR, western blotting, and immunofluorescent assays determined the intracellular viral RNA and protein expression. For viral productivity, we utilized plaque assays to confirm the antiviral properties of resveratrol against MERS-CoV. Results Resveratrol significantly inhibited MERS-CoV infection and prolonged cellular survival after virus infection. We also found that the expression of nucleocapsid (N) protein essential for MERS-CoV replication was decreased after resveratrol treatment. Furthermore, resveratrol down-regulated the apoptosis induced by MERS-CoVin vitro . By consecutive administration of resveratrol, we were able to reduce the concentration of resveratrol while achieving inhibitory effectiveness against MERS-CoV. Conclusion In this study, we first demonstrated that resveratrol is a potent anti-MERS agentin vitro . We perceive that resveratrol can be a potential antiviral agent against MERS-CoV infection in the near future.